Skin Metastasis of Sarcomatoid Squamous Cell Carcinoma in Vulva A Case Report - Cüneyt Taner; İrem Şenyuva; Elif Üstünay; Sibel Keçeli; Duygu Ayaz (Medical Network, 2009)
Histopathologic results and clinical course of the sarcomatoid-type vulvar squamous cell carcinoma presenting skin metastasis which is an uncommon entity. Patient presented a nodular lesion of 1cm diameter in right labium minus. Pathology results revealed squamous cell carcinoma. Radical vulvectomy, bilateral inguinofemoral lymphadenectomy were applied to the case. Sarcomatoid squamous cell carcinoma and metastasis in the lymph nodes. Postoperative radiotherapy was applied. The patient again presented 4 months later due to a nodular lesion in the inguinal region. Squamous cell carcinoma displaying sarcomatoid alterations in the dermis. the case was subjected to extended field radiotherapy and cisplatin chemotherapy. The patient's condition deteriorated postoperative 5th month. Survival rate for skin metastasis of sarcomatoid squamous cell carcinoma in vulva, is found to be poor.